Synthesis, Structural Characterization and Photocatalytic Activity of Iron-Doped Titanium Dioxide Nanopowders - Castillo, Jordana H.; Rodriguez, Francisco J.; López-Malo, Aurelio; Sanchez-Mora, Enrique; Quiroz, Marco A.; Bandala, Erick R. (Journal of Technology Innovations in Renewable Energy, 2015)
Iron-doped TiO2 nanopowders with different doping amounts have been prepared by co-precipitation method followed by heat treatment. The obtained materials were structurally, morphologically and analytically characterized by X-ray diffraction (XRD), FT-Raman spectroscopy, diffuse reflectance spectroscopy (DRS) and energy dispersive X-ray spectroscopy (EDX) coupled to scanning electron microscopy (SEM). XRD analysis revealed the major presence of the anatasa crystalline phase for iron-doped and undoped TiO2. SEM confirmed particles sizes among the nanometer scale along with XRD data. The presence of iron ions was validated by EDX-SEM. Diffuse reflectance techniques were carried out to validate the shift of the band edge absorption spectrum of doped TiO2 nanoparticles towards the visible region and to confirm the presence of iron atoms in the TiO2 crystal lattice by the resulting variation of the band gap value of the doped materials. Photocatalytic activity of the nanoparticles under UV and visible radiation was evaluated by means of hydroxyl radicals production through indirect estimation using N,N-dimethyl-p-nitrosoaniline (PNDA)photo-discoloration experiments in aqueous dispersion. Samples containing 1.2 and 5.6 weight % Fe exhibited the highest activities in this study for both conditions.